Computational Study of the Surface‐Enhanced Raman Scattering from Silica‐Coated Silver Nanowires1. (8th December 2013) - DeVetter, Brent M.; Bhargava, Rohit; Murphy, Catherine J.
Abstract Surface‐enhanced Raman scattering (SERS) is a popular vibrational spectroscopic technique that can have several applications in chemical and biological sensing. Within the last decade or so, our ability to chemically synthesize nanostructures has improved to the point that the rational design of a variety of SERS substrates is now viable. In this report, we describe a computational study using the finite element method (FEM) to investigate the effects of patchy silica coatings on silver nanowires. We found that varying the degree of silica coating on silver nanowires impacts the enhancement and may be explained through two processes. The first process is a consequence of changes in the dielectric environment surrounding the nanowire due to the silica. As additional layers of silica coat the nanowire, the localized surface plasmon resonance of the nanowire redshifts. The second process is a result of silica distorting the local electric field around the nanowire surface. Anisotropic silica coating can influence anticipated enhancement depending on its spatial localization with respect to excited plasmon modes in the nanowire. We propose that the design of nanostructures with patchy silica coatings can be a viable tool for increasing surface enhancement.